PENGARUH PEMAHAMAN PERATURAN PERPAJAKAN, KESADARAN WAJIB PAJAK DAN SIKAP FISKUS TERHADAP KEPATUHAN WAJIB PAJAK DALAM MEMBAYAR PAJAK KENDARAAN BERMOTOR DI KABUPATEN WONOGIRI - Gadit Aryo Sadewo; Kurnia Rina Ariani (Journal of Innovation Research and Knowledge, 2025)
Since more people are riding motorcycles every year, there are also more people who are breaking the law. The purpose of this study is to ascertain if motorized motorists' compliance with tax laws is impacted by their knowledge of tax laws, their awareness of them, and the attitude of tax officials. This study's methodology is quantitative in nature. A motorized vehicle taxpayer who is registered at the Wonogiri SAMSAT Office provides the data. Accidental sampling is the sample technique employed in this investigation. Likert scales and documentation are included in the collection process. Validity tests, testing, multiple linear regression analysis, autocorrelation, heteroscedasticity, normality, F statistical tests, t tests, determination coefficient tests (R2), and classical assumption tests are all carried out using SPSS 25. 1) Taxpayer compliance is significantly improved by an understanding of tax rules, according to the study's findings. 2) The impact of taxpayer knowledge on taxpayer compliance is substantial. 3) All motor vehicle taxpayers registered at the Wonogiri Regency SAMSAT Office said that their Taxpayer Compliance was significantly improved by the tax authorities' attitude